A feasible classification method of wet masses to predict pellet formation of powdered herbal slices (Brazilian Journal of Pharmaceutical Sciences, 2022)
The aim of the current study was to explore the correlation between physical properties of wet masses and pellet quality by using powdered herbal slices as model drugs. Wet masses with 100 formulations were prepared by taking 20 kinds of powdered herbal slices as model drugs, microcrystalline cellulose as pelletization aid and five levels of added water as liquid binder. Physical properties of the wet masses such as hardness, adhesiveness, springiness, cohesiveness, chewiness, and resilience were measured by a texture analyzer. Meanwhile, the moisture retention capacities (MRC) of powdered herbal slices and wet masses were determined. Particles were classified after they were produced during spheronization. Principal component analysis, factor analysis and classification analysis were performed on the data. Wet masses could be classified into three groups by taking Ha as the first classification index and Ha/Sp as the second classification index. The correct rate of the classification was 91.00%. If Ha value of wet masses was greater than 15610 g, pellets of type ① would form, otherwise, pellets of type ② or type ③ would form based on Ha/Sp value. Then a classification plot of wet masses was developed to predict pellet formation of powdered herbal slices. Meanwhile, theprobable mechanism of pellets formation during spheronisation was concluded in this study, which provided useful information to improve pellet quality.